The Effects of Ursolic Acid Treatment on Immunopathogenesis Following Mannheimia haemolytica Infections - Slate, Jamison R.; Chriswell, Bradley O.; Briggs, Robert E.; McGill, Jodi L. (Frontiers in Veterinary Science, 2021)
Bovine respiratory disease complex (BRDC) is a costly economic and health burden for the dairy and feedlot cattle industries. Mannheimia haemolytica (MH) is common commensal bacteria found in the nasopharynx of healthy cattle; however, following environmental and immunological stressors, these bacteria can rapidly proliferate and spread to the lower respiratory tract, giving rise to pneumonic disease. Severe MH infections are often characterized by leukocyte infiltration and dysregulated inflammatory responses in the lungs. IL-17A is thought to play a key role in this inflammatory response by inducing neutrophilia, activating innate and adaptive immune cells, and further exacerbating lung congestion. Herein, we used a small molecule inhibitor, ursolic acid (UA), to suppress IL-17A production and to determine the downstream impact on the immune response and disease severity following MH infection in calves. We hypothesized that altering IL-17A signaling during MH infections may have therapeutic effects by reducing immune-mediated lung inflammation and improving disease outcome. Two independent studies were performed (Study 1 = 32 animals, and Study 2 = 16 animals) using 4-week-old male Holstein calves, which were divided into 4 treatment group including: 1) non-treated and non-challenged, 2) non-treated and MH-challenged, 3) UA-treated and non-challenged, and 4) UA-treated and MH-challenged. Based on the combined studies, we observed a tendency (p = 0.0605) towards reduced bacterial burdens in the lungs of UA-treated animals but did not note a significant difference in gross (p = 0.3343) or microscopic (p = 0.1917) pathology scores in the lungs. UA-treatment significantly altered the inflammatory environment in the lung tissues following MH infection, reducing the expression of IL-17A (p = 0.0870), inflammatory IL-6 and STAT3 (p = 0.0209 and 0.0205 respectively) compared to controls. This reduction in IL-17A signaling also appeared to alter the downstream expression of genes associated with innate defenses (BAC5, DEFB1, and MUC5AC) and lung remodeling (MMP9 and TIMP-1). Taken together, our results support our hypothesis that IL-17A signaling may contribute to lung immunopathology following MH infections, and that further understanding this inflammatory pathway during BRDC could expand therapeutic intervention strategies for managing BRDC.